Definition, diagnosis, and management of COVID-19-associated pulmonary mucormycosis: Delphi consensus statement from the Fungal Infection Study Forum and Academy of Pulmonary Sciences, India. Issue 9 (September 2022) - Muthu, Valliappan; Agarwal, Ritesh; Patel, Atul; Kathirvel, Soundappan; Abraham, Ooriapadickal Cherian; Aggarwal, Ashutosh Nath; Bal, Amanjit; Bhalla, Ashu Seith; Chhajed, Prashant N; Chaudhry, Dhruva; Garg, Mandeep; Guleria, Randeep; et al.
Summary: COVID-19-associated pulmonary mucormycosis (CAPM) remains an underdiagnosed entity. Using a modified Delphi method, we have formulated a consensus statement for the diagnosis and management of CAPM. We selected 26 experts from various disciplines who are involved in managing CAPM. Three rounds of the Delphi process were held to reach consensus (≥70% agreement or disagreement) or dissensus. A consensus was achieved for 84 of the 89 statements. Pulmonary mucormycosis occurring within 3 months of COVID-19 diagnosis was labelled CAPM and classified further as proven, probable, and possible. We recommend flexible bronchoscopy to enable early diagnosis. The experts proposed definitions to categorise dual infections with aspergillosis and mucormycosis in patients with COVID-19. We recommend liposomal amphotericin B (5 mg/kg per day) and early surgery as central to the management of mucormycosis in patients with COVID-19. We recommend response assessment at 4–6 weeks using clinical and imaging parameters. Posaconazole or isavuconazole was recommended as maintenance therapy following initial response, but no consensus was reached for the duration of treatment. In patients with stable or progressive disease, the experts recommended salvage therapy with posaconazole or isavuconazole. CAPM is a rare but under-reported complication of COVID-19. Although we have proposed recommendations for defining, diagnosing, and managing CAPM, more extensive research is required.